Assessment of Fetal Congenital Heart Diseases by 4-Dimensional Ultrasound Using Spatiotemporal Image Correlation: Pictorial Review. Issue 1 (March 2018) - Araujo Júnior, Edward; Tonni, Gabriele; Bravo-Valenzuela, Nathalie Jeanne; Da Silva Costa, Fabricio; Meagher, Simon
Abstract : Abstract: The aim of this pictorial review is to describe the technical advances achieved through the application of 4-dimensional (4D) ultrasound using spatiotemporal image correlation (STIC) over conventional 2-dimensional ultrasound in the prenatal detection of congenital heart disease (CHD). Spatiotemporal image correlation is a volume imaging technique that simplifies fetal heart studies while providing more diagnostic information than is typically available from traditional 2-dimensional studies. Four-dimensional software allows the study of cardiac anatomy and function during a single cardiac cycle and has greatly contributed to diagnostic enhancement of CHD. Color flow and power Doppler can be added to STIC in the study of vessel anatomy and to increase the detection of ventricular septal defects. Anatomical details of the fetus can be displayed in multiple images such as using computed tomography or magnetic resonance imaging. In addition, cardiac anatomy can be sectioned freely and reconstructed using different reformatting applications. Realistic views of the fetal heart, with particular emphasis on myocardium and endocardium cushion, can be reached using novel lightening techniques. Moreover, using 4D ultrasound, echolucent structures can be converted into solid voxels generating "digital casts" of the fetal heart that enhances the understanding of the great vessel relationships in the ventricular inflow and outflow tracts. Recently, sillhouette mode has shown to improve depth perception and resolution compared with conventional 3D power Doppler in the study of inflow and outflow tracts. Here, a gallery of prenatally detected CHD using 4D ultrasound with STIC and different applications is described. Abstract : Supplemental digital content is available in the text.